Noise and spirit: the religious and spiritual sensibilities of rap music - Pinn, Anthony B. (New York University Press, 2003)
Introduction : Making a world with a beat : musical expression's relationship to religious identity and experience -- Rap and religious traditions. African American Christian rap : facing "truth" and resisting it / Garth Kasimu Baker-Fletcher. A jihad of words : the evolution of African American Islam and contemporary hip hop / Juan M. Floyd-Thomas. Rap, reggae, and religion : sounds of cultural dissonance / Noel Leo Erskine. "Handlin' my business" : exploring rap's humanist sensibilities / Anthony B. Pinn -- Rap and issues of "spirit" and "spirituality." Bringing noise, conjuring spirit : rap as spiritual practice / Mark Lewis Taylor. Rap as wrap and rapture : North American popular culture and the denial of death / James W. Perkinson. The spirit is willing and so is the flesh : the queen in hip hop culture / Leola A. Johnson -- Rap and the art of "theologizing." The rub : markets, morals, and the "theologizing" of music / William C. Banfield. Rap, religion, and new realities : the emergence of a religious discourse in rap music / Ralph C. Watkins.